Analisis Optimalisasi Strategi Pemasaran Home Industry Kerupuk Desa Punggul Sidoarjo - Basya, Maziyah; Sabrina, Salwa (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Punggul Sidoarjo Village is known for its many MSMEs in the form of home industries whose existence is able to empower the surrounding community, one of which is the Pak Muncul cracker industry which not only supports the local economy by opening employment opportunities for Punggul village residents, but is also part of the wider context in Gedangan sub-district. This research aims to determine internal and external factors based on SWOT analysis and to determine the right marketing strategy as a form of optimization in increasing turnover in Pak Muncul's cracker industry. This research uses a qualitative approach with a case study type of research. The results of this research show that the position of the Pak Muncul cracker industry is in quadrant I. The approach that must be applied in this position is Growth Oriented Strategy